2001
DOI: 10.1007/s002940000165
|View full text |Cite
|
Sign up to set email alerts
|

l -Sorbose induces cellulase gene transcription in the cellulolytic fungus Trichoderma reesei

Abstract: L-Sorbose has previously been assumed to stimulate cellulase formation in an indirect manner, different from that of sophorose in Trichoderma reesei. Through Northern blot analysis however, L-sorbose was found to regulate coordinately six cellulase genes (including eg13, whose behavior has not been studied so far) at transcriptional level, as is the case with sophorose in T. reesei strains PC-3-7 and QM9414. Dot blot analysis showed that the proportions of each cellulase mRNA to cbh1 mRNA, the largest amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 0 publications
3
52
0
4
Order By: Relevance
“…Previous studies (19,20,32) have shown that the known cellulase components and some hemicellulases are coordinately induced by certain substrates. The large magnitude in induction of genes encoding cellulase components and the toll on cellular resources used in synthesizing them suggests that the tendency toward tight coordinate regulation is likely to hold true for other genes whose products are involved in biomass degradation or in facilitating their synthesis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies (19,20,32) have shown that the known cellulase components and some hemicellulases are coordinately induced by certain substrates. The large magnitude in induction of genes encoding cellulase components and the toll on cellular resources used in synthesizing them suggests that the tendency toward tight coordinate regulation is likely to hold true for other genes whose products are involved in biomass degradation or in facilitating their synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…Regulation of the Endoglucanases and the ␤-GlucosidasesThe previously identified endoglucanases are induced during growth on media containing cellulose, sophorose, or lactose (13,19,20). To determine whether the newly discovered endoglucanases are similarly regulated, we examined mRNA levels for each of these gene products by Northern blot.…”
Section: Identification Of New Genes Encoding Hydrolytic Enzymes-mentioning
confidence: 99%
See 1 more Smart Citation
“…16) In the case of cellulase production in Tricoderma, cellulose and its degraded oligosaccharides or sophorose are reported as inducers. 17,18) The above studies indicate that fungal extracellular polysaccharide hydrolytic enzymes use the substrates or those degraded products as inducers for the enzyme production. On the other hand, the protease used in this study did not require proteins or those degraded products as the inducer, but highly branched glucan as an inducer.…”
Section: Discussionmentioning
confidence: 99%
“…Since cellulase formation is triggered by sporulation (Kubicek, 1987), γ-aminobutyrate may constitute a link between cellulase induction and conidiation. On the other hand, the increased utilization of D-sorbitol by the improved producer strain QM 9414 may be linked to enhanced formation of L-sorbose, an inducer of cellulase formation in H. jecorina (Nogawa et al, 2001), because it is formed from D-sorbitol by the respective nicotinamide adenine dinucleotide phosphate (NADP)-dependent ketose reductase (Seiboth et al, 2007). While the importance of these two findings for cellulase production must be verified by reverse genetics, they have nevertheless pointed to two biochemical reactions, which may have a major impact on cellulase formation, and would have remained undetected without PM analysis.…”
Section: Identification Of Phenetic Differences In Non-transformed Mumentioning
confidence: 99%